The Hidden Notes of Redox Balance in Neurodegenerative Diseases - Silvia Piccirillo; Simona Magi; Alessandra Preziuso; Tiziano Serfilippi; Giorgia Cerqueni; Monia Orciani; Salvatore Amoroso; Vincenzo Lariccia (MDPI AG, 2022)
Reactive oxygen species (ROS) are versatile molecules that, even if produced in the background of many biological processes and responses, possess pleiotropic roles categorized in two interactive yet opposite domains. In particular, ROS can either function as signaling molecules that shape physiological cell functions, or act as deleterious end products of unbalanced redox reactions. Indeed, cellular redox status needs to be tightly regulated to ensure proper cellular functioning, and either excessive ROS accumulation or the dysfunction of antioxidant systems can perturb the redox homeostasis, leading to supraphysiological concentrations of ROS and potentially harmful outcomes. Therefore, whether ROS would act as signaling molecules or as detrimental factors strictly relies on a dynamic equilibrium between free radical production and scavenging resources. Of notice, the mammalian brain is particularly vulnerable to ROS-mediated toxicity, because it possesses relatively poor antioxidant defenses to cope with the redox burden imposed by the elevated oxygen consumption rate and metabolic activity. Many features of neurodegenerative diseases can in fact be traced back to causes of oxidative stress, which may influence both the onset and progression of brain demise. This review focuses on the description of the dual roles of ROS as double-edge sword in both physiological and pathological settings, with reference to Alzheimer's and Parkinson's diseases.